Drug management system (DMS) - Nurul Ain, Muhammad (2010)
Every organization possesses its 'own method in managing and controlling the inventory system. A study over inventory management has been carrying out at Pharmacy, Klinik Kesihatan Beris Panchor in order to develop a Drug Management System (DMS). This system therefore will resolve and replace the current system process besides increasing the inventory management system in order to produce an effective and efficient system. DMS is equipped with the automated alert features. It able to remind the admin (pharmacist officer) about list of the drug reached the minimum quantity and also support reminder for the expired date for each drug. This system is a web based system that will be developed using Adobe Dreamweaver CS4, Hypertext Preprocessor (PHP), Apache Web Server and MySQL as the system's database. The system development methodology that will be used is System Development Life Cycle :(SDLC) Hopefully, this system that will be developed can help Pharmacy, Klinik Kesihatan Beris Panchor to handle the incoming and outgoing inventories more smoothly and in a better way.